MCS51® Evaluation Tool with IDE Approach for Learning Environment - The UMP-MET - Selvakumar, Raja Saravana Kumar; Kamarul Hawari, Ghazali; Nik Mohd Kamil, Nik Yusof (2010)
According to the latest survey, more than half of the total student in Faculty of Electrical & Electronics Engineering are having problem in understanding program structure and developing hardware. For this reason, the MCS51Â® microcontroller development project is designed to be as a learning tool for those who intend to learn microcontroller. With an extensive a development board, it could let the user to get start with their microcontroller application efficiently. Without wasting too much time in preparing prototype circuit is one of the advantages by using a development board. In addition, the MCS51Â® Evaluation Tool (UMP-MET) teaches the general applications of development board. Therefore, the users could just get start with their software development if their applications are found in the UMP-MET. As a learning tool, it could let the student to test their software on UMP-MET. By using The UMP-MET, the users will be able to learn from this practical experience. In this respect, the UMP-MET would be applicable for education and expose the electrical engineering students to the understanding of microcontroller in electronic design field.